2014
DOI: 10.1017/s0003055413000592
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Birth Factors, Post-Birth Factors, and Voting: Evidence from Swedish Adoption Data

Abstract: This paper analyzes a rich Swedish data set with information on the electoral turnout of a large sample of adoptees, their siblings, their adoptive parents, and their biological parents. We use a simple regression framework to decompose the parent-child resemblance in voting into pre-birth factors, measured by biological parents' voting, and post-birth factors, measured by adoptive parents'voting. Adoptees are more likely to vote if their biological parents were voters and if they were assigned to families in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 54 publications
(143 reference statements)
1
49
2
Order By: Relevance
“…Corak and Piraino (2011) study the intergenerational transmission of employers. Thompson (2014) studies the transmission of health and Cesarini et al (2014) study the transmission of voting behaviour.…”
Section: Datamentioning
confidence: 99%
“…Corak and Piraino (2011) study the intergenerational transmission of employers. Thompson (2014) studies the transmission of health and Cesarini et al (2014) study the transmission of voting behaviour.…”
Section: Datamentioning
confidence: 99%
“…The adoption methodology (and subsequent sensitivity analyses) we use was pioneered by Björklund et al (2006) who studied the intergenerational transmission of income and education. Other recent papers using the Björklund et al (2006) methodology and similar data include Hjalmarsson and Lindquist (forthcoming) who study intergenerational correlations in crime and Cesarini et al (2012) who study voting behavior.…”
mentioning
confidence: 99%
“…Since then, the Swedish data have been used to study voting (Cesarini, Johannesson, and Oskarsson, 2014), crime (Hjalmarsson and Lindquist, 2013), entrepreneurship (Lindquist, Sol, and Van Praag, 2015), and health (Lindahl et al 2015). These studies have found evidence that both characteristics of biological and adoptive parents are predictive of child outcomes.…”
Section: Empirical Strategymentioning
confidence: 99%